2004
DOI: 10.1063/1.1810205
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage shift in organic field effect transistors by dipole monolayers on the gate insulator

Abstract: We demonstrate controllable shift of the threshold voltage and the turn-on voltage in pentacene thin film transistors and rubrene single crystal field effect transistors (FET) by the use of nine organosilanes with different functional groups. Prior to depositing the organic semiconductors, the organosilanes were applied to the SiO2 gate insulator from solution and form a self assembled monolayer (SAM). The observed shift of the transfer characteristics range from -2 to 50 V and can be related to the surface po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

37
492
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 531 publications
(531 citation statements)
references
References 53 publications
37
492
0
1
Order By: Relevance
“…Shifts in V T similar to the shift caused by QBP under neutral assembling conditions have also been reported by using SAMs. 4,5 However, the ability to vary assembling conditions of the peptide offers an efficient method for controlling V T .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts in V T similar to the shift caused by QBP under neutral assembling conditions have also been reported by using SAMs. 4,5 However, the ability to vary assembling conditions of the peptide offers an efficient method for controlling V T .…”
mentioning
confidence: 99%
“…3,4 It can be shifted by modifying the dielectric with self assembled monolayers ͑SAMs͒ to shift V T by tens of volts. 5,6 A less studied route in the pursuit of improved device performance involves integrating functional biological materials into OTFTs. 7 Singh et al demonstrated using deoxyribonucleic acid as a gate dielectric to produce memory effect.…”
mentioning
confidence: 99%
“…V T voltage additionally has been found to depend strongly on the preparation of the surface on which the organic material is deposited. Threshold voltage shifts in thin film as well as single−crystal OFETs have been found to be induced by di− pole monolayers on the gate insulator [41]. Thickness of the semiconductor layer influences the values of the threshold voltage and, to a lesser extent, the saturation current.…”
Section: Threshold Voltagementioning
confidence: 99%
“…This has been achieved by modifying a parylene gate dielectric with oxygen plasma [9] or a UV-ozone [10] treatment, or by inserting a layer of metal oxide in the transistor structure [11]. Also, thin siloxane layers have been found to significantly modify the threshold voltage [12,13].…”
Section: Introductionmentioning
confidence: 99%